Synergistic Efficacy of Integrated Care (Syzygium Jambolanum + Conventional Therapy) Vs Conventional Therapy Alone In Managing Type 2 Diabetes Mellitus: Randomised Controlled Trial – A Case Study - Jha, Preeti; Trigotra, Dushant; Bishwas, Rinku (Journal of Neonatal Surgery, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by persistent hyperglycemia resulting from insulin resistance and/or impaired insulin secretion. Despite the availability of conventional therapies, achieving optimal glycemic control remains challenging in many patients. Syzygium jambolanum, a well-known homoeopathic medicine, has traditionally been used in the management of diabetes. This study explored the synergistic efficacy of integrated care (Syzygium jambolanum along with conventional therapy) compared with conventional therapy alone in patients with Type 2 Diabetes Mellitus over a 6-month follow-up period. Aim: To study the efficacy of integrated care (Syzygium jambolanum + conventional therapy) versus conventional therapy alone in the management of Type 2 Diabetes Mellitus. Objectives: To assess the efficacy of integrated care in cases of Type 2 Diabetes Mellitus using glycemic parameters before and after treatment. To compare the changes in HbA1c, fasting blood glucose (FBG), and postprandial blood glucose (PPBG) between the integrated care group and the conventional therapy group. • To evaluate the safety and tolerability of integrated care in patients with Type 2 Diabetes Mellitus